Phytochemical composition and antimicrobial potential of Stevia rebaudiana Bertoni extract and its topical spray formulation against animal skin pathogens - Ranee Singh; Glenn Neville Borlace; Patchanee Sringam; Eakachai Thongkham; Jareerat Aiemsaard (Veterinary World)
Background and Aim: The rise of antimicrobial resistance in veterinary medicine is a significant concern, particularly for pathogens responsible for skin infections. Although Stevia rebaudiana Bertoni (stevia) has demonstrated effective antimicrobial properties, there is limited research on its efficacy against animal skin pathogens. This study aimed to identify natural compounds in stevia extract, develop a topical spray formulation, and assess its effectiveness against six common bacterial and fungal pathogens associated with animal skin infections.